Peacebuilding in the Asia-Pacific
XXV, 261 p. 5 illus. in color.
Keywords: This book explores theories of conflict and peacebuilding and applies them to case studies from the Asia Pacific region, seeking to shift attention to the inherency of conflict, the constant danger of re-emergence, and the need to establish mechanisms to resolve it. The authors argue that the central focus of peacebuilding should not be state-building per se, but rather the creation of effective mechanisms for peaceful resolution of both past and newly emerging conflicts. To do so, it is important to consider the entire process of creating peace, to contemplate the linkages between conflict, resolution, and post-conflict peacebuilding, rather than focus only on the period of institution-building. Carmela Lutmar is Visiting Lecturer at New York University, USA, and Lecturer in the Division of International Relations in the School of Political Sciences at the University of Haifa, Israel. James Ockey isAssociate Professor in the Department of Political Science and International Relations at the University of Canterbury, New Zealand.